Analisis Reaksi Pasar Modal di Asia Tenggara terhadap Pandemi COVID – 19 - Herlina, Beti; Husaini; Fitrawati Ilyas (Edupedia Publisher, 2024)
This study aims to find empirical evidence regarding the Capital Market Reaction Analysis in Southeast Asia to the Covid-19 Pandemic. This study uses abnormal stock returns obtained from the composite stock index on the stock market in each Southeast Asian country in 2019 (before the pandemic occurred) and 2020 (when the Covid-19 pandemic occurred). The type of research used in this research is comparative quantitative research and the method used is descriptive quantitative. The research population is countries that have been affected by the Covid-19 pandemic. The sample of this research is the stock market in Thailand, Singapore, Vietnam, Malaysia, Cambodia, the Philippines, Indonesia, Myanmar, and Laos. Based on the results of the Abnormal Stock Return test using the Paired Sample t – Test, only Cambodia has reacted to the Covid-19 pandemic. Meanwhile, Thailand, Singapore, Vietnam, Malaysia, the Philippines, Indonesia, Myanmar, and Laos have not reacted to the Covid-19 pandemic. So it can be concluded that the hypothesis in this study was rejected. This means that there is no significant difference in the comparison of abnormal stock returns before and during the Covid-19 pandemic. This proves that the Covid-19 pandemic does not yet have significant information content to affect the stock market in Southeast Asia.